Athletes' perspective on parental involvement, motivation, and performance throughout a football season - Morais, C.; Gomes, A. R.; Teixeira, M.; Branco, C. (Journal of Physical Education and Sport, 2025)
Problem Statement: Athletes` goal orientation is a widely-studied topic in sports because motivation significantly influences sport participation and overall development. According to Achievement Goal Theory (AGT), athletes adopt either a task/mastery orientation - where success is determined by continuous development - or an ego orientation, where success is determined by comparison to others` performance. These orientations impact athletes` effort, perseverance and, ultimately, their performance. However, goal orientation is not only intrinsic; it can also be shaped by parental behaviors and involvement in sports. The present study tests the assumption that athletes` perception of parental involvement affects their goal achievement orientation, which, in turn, predicts their performance.